PARTISIPASI ANGGOTA KPM DALAM MENGIKUTI KEGIATAN PENGAJIAN PKH DI DESA PANDAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Sri Rahayu; Titi Maemunaty; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the participation of KPM members in participation in the PKH study activities in Pandau Jaya Village, Siak Hulu district, Kampar District. This study uses a descriptive method with a quantitative approach. The sample in this study was 50 people, namely KPM members with a random sampling technique according to the Slovenian formula. The technique to collect data using a questionnaire. Data analysis techniques using the percentage formula. The results of this study show that the participation in thinking is quite high, the participation of employees is quite high, the participation of real estate is quite high, the participation of the skills provided is quite high, social participation given as very close proximityKey Words: Participation, KPM members in following the PKH study.